Attitudes and willingness of local communities towards natural urban forest conservation in a rapidly developing Southeast Asia city. (October 2022) - Aiman, Arief; Aziz, Nor Akmar Abdul; Saadun, Norzanalia; Lin, Evelyn Lim Ai; Lechner, Alex M.; Azhar, Badrul
Abstract: Habitat fragmentation is a major threat to natural forests, causing unprecedented biodiversity loss and habitat destruction. To date, the social-economic factors affecting the conservation of fragmented urban forest remnants have been rarely investigated, particularly in the tropics. The objective of this study is to understand the attitudes and willingness to conserve natural urban forests in local communities living nearby. We interviewed 450 respondents living near three natural urban forests in Greater Kuala Lumpur, Malaysia, using a structured questionnaire. We found that the majority of the respondents had a positive attitude towards natural urban forest conservation. Local communities had high willingness to conserve these natural urban forest patches. The main contributing factors to attitudes and willingness were the presence of forest patches in their neighbourhood, education level, and length of stay. The relationships between urban forests and humans are complex, as this study demonstrates. Regardless of patch size, the local communities were concerned about the conservation of natural urban forest patches and their ecological integrity. Our findings can inform policy-makers to support better planning of urban green spaces and biodiversity conservation, which are especially important for cities in low and middle income countries in the Global South. Highlights: Fragmentation is causing biodiversity loss and habitat destruction in the tropics. Socio-demographic variables shape environmental attitudes and willingness. Public attitudes and willingness support urban forest conservation. Local communities care about urban forest patches regardless of the patch sizes. Our findings improve planning of urban green spaces and biodiversity conservation.